Model Pemberdayaan Petani Berbasis Pusat Pelatihan Pertanian Swadaya dalam Mendukung Kemandirian Pangan di Kabupaten Karo - Lubis, Anita Rizky; Hasibuan, Surtan; Zendrato, Melvin; Ginting, Nelva Meyriani Br (Jurnal Social Economic of Agriculture, 2025)
The utilisation of the Independent Agricultural Training Centre (PPPS) in Karo Regency is urgently needed. Karo Regency, which often faces food security challenges, can rely on PPPS to increase local agricultural production, reduce dependence on food imports, and strengthen food self-sufficiency. By empowering farmers through training and technical guidance, PPPS can be a driving force for sustainable agricultural development and food security in the region. The objectives of this study are to identify the existing conditions of P4S in Karo Regency, measure the level of farmer independence in terms of food production, distribution, and consumption, and formulate an effective P4S-based farmer empowerment model. The method used is a qualitative approach. The first objective uses the Participatory Rural Appraisal (PRA) method through social mapping, timeline, and scoring. The second objective uses Q Methodology (Q-Sort), and the empowerment model is carried out through Soft Systems Methodology (SSM). The results of the study show that the existing P4S in Karo Regency plays an important role in increasing farmers' technical capacity, but is still weak in terms of market access, capital, and institutions. The level of farmer independence shows variation: relatively independent in production and consumption, but still dependent on middlemen in distribution. A P4S-based empowerment model was formulated to strengthen the role of P4S as a link between farmers and the government, markets, financial institutions, and technology providers, in order to promote more comprehensive farmer independence.